An unusual cause of urinary retention: A nineteen-year-old surgical gauze in the bladder - (:unkn) unknown (My University, 2002)
Intravesical foreign body is a significant consideration in the assessment of lower urinary tract problems. We present a case of foreign body in the urinary bladder with the longest interval in the literature for clinical presentation, about 19 years following a transvesical prostatectomy. It provides an unusual indolent cause of urinary retention and stresses the consideration of intravesical foreign bodies as a reason for lower urinary tract symptoms.
Keywords: Bladder; Case report; Foreign body